Pengaruh Diskon Harga Dan Testimoni Konsumen Terhadap Keputusan Pembelian Produk Flimty Fiber Pada Member Central Gym Galaxy Di Bekasi - Hiltza Huzaematul Al Aswad; Widi Winarso; Kardinah Indrianna Meutia (Universitas 45 Surabaya, 2024)
This research aims to determine the influence of price discounts and consumer testimonials on purchasing decisions for Flimty Fiber products among Central Gym Galaxy members in Bekasi. This type of research is quantitative. The population in this study is unknown. The sampling technique uses Non-Probability Sampling using Purposive Sampling techniques. The sample in this study amounted to 104 respondents. Data collection technique by distributing questionnaires via Google Form. Hypothesis testing in this research uses Multiple Linear Regression analysis. The research subjects are Flimty Fiber consumers. The results of this research show that the price discount variables and consumer testimonials partially and simultaneously have a significant effect and have a positive influence on the purchasing decision variable.